PENGARUH STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PADA CV. GRAHA MINERAL SIBOLGA (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to examine the effect of capital structure/DER (X) on CV.Graha Mineral Sibolga. The author uses research methods in quantitative descriptive to discuss the problems faced by corporate finance. Data analysis explained the use of the results of several linear sub-data analyzes regarding the quick ratio (lancer ratio) to financial performance/ROA (Y). The results showed that there was a positive relationship between the quick ratio and return on equity at CV.Graha Mineral Sibolga of 0.898, so when interpreted on a value scale it can be categorized as very strong. The regression equation obtained Y = 1.112 + 0.646 X which shows the effect of capital structure/DER on financial performance at CV. Graha Mineral Sibolga. The t test shows that the hypothesis proposed is rejected (not significant), where t count is -3.536 > 2.07387, which means that financial performance/ROA is not necessarily reduced by the regression coefficient/slop (-0.646) if the capital structure/DER variable is added one unit. While the coefficient of determination is known that the capital structure/DER only plays a role of 80.6% of the financial performance of CV. Graha Mineral Sibolga and the remaining 19.4% is influenced by other factors not included in the model.